2005
DOI: 10.1074/jbc.m503614200
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Hsp110 Sse1 Functionally Interacts with the Hsp70 Chaperones Ssa and Ssb

Abstract: There is growing evidence that members of the extended Hsp70 family of molecular chaperones, including the Hsp110 and Grp170 subgroups, collaborate in vivo to carry out essential cellular processes. However, relatively little is known regarding the interactions and cellular functions of Sse1, the yeast Hsp110 homolog. Through co-immunoprecipitation analysis, we found that Sse1 forms heterodimeric complexes with the abundant cytosolic Hsp70s Ssa and Ssb in vivo. Furthermore, these complexes can be efficiently r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
123
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(138 citation statements)
references
References 43 publications
15
123
0
Order By: Relevance
“…6B). As we previously demonstrated, Sse1 strongly interacted with both Hsp70s (22). In contrast, Fes1 appeared to interact exclusively with Ssa in vivo, with only background amounts of Ssb co-purifying.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…6B). As we previously demonstrated, Sse1 strongly interacted with both Hsp70s (22). In contrast, Fes1 appeared to interact exclusively with Ssa in vivo, with only background amounts of Ssb co-purifying.…”
Section: Resultssupporting
confidence: 52%
“…Sse1 has been implicated in Hsp70-mediated protein folding at the ribosome, Hsp90 chaperoning of signal transduction, and post-translational translocation of pre-pro ␣-factor (21,22,37,38). Both Sse1 and Fes1 participate in Hsp70-dependent ubiquitination and degradation of misfolded proteins (39 -43).…”
mentioning
confidence: 99%
“…A number of studies suggested that Hsp110s participate in many processes associated with cytosolic Hsp70s, including de novo protein folding, refolding under stress, translocation into the endoplasmic reticulum, degradation, and prion formation (24 -31). Consistent with these observations, Hsp110s have recently been shown to form complexes with cytosolic Hsp70s for which they function as the major NEF (25,(32)(33)(34)(35). Moreover, the corresponding mechanism of this nucleotide exchange activity was recently revealed by a number of biochemical and crystallographic studies (36 -39).…”
mentioning
confidence: 67%
“…Interestingly, mammalian Hsp110 has been reported to inhibit the ATPase activity of nucleotide-loaded Hsp70 (29), which could be consistent with an Hsp110 nucleotide exchange activity. In addition, Shaner et al (49) report that Sse1p can stimulate the ATPase of SSA in conjunction with its J-protein Ydj1. Because nucleotide exchange by Hsp70 promotes polypeptide release, the suggestion that Sse1p may act as a nucleotide exchange factor is consistent with our functional analysis.…”
Section: Distinct Roles Of Cytosolic Hsp70s In De Novomentioning
confidence: 99%